Early Tracheostomy Is Associated With Shorter Ventilation Time and Duration of ICU Stay in Patients With Myasthenic Crisis—A Multicenter Analysis. (January 2022) - Angstwurm, Klemens; Vidal, Amelie; Stetefeld, Henning; Dohmen, Christian; Mergenthaler, Philipp; Kohler, Siegfried; Schönenberger, Silvia; Bösel, Julian; Neumann, Ursula; Lee, De-Hyung; Gerner, Stefan T.; Huttner, Hagen B.; et al.
Background: Myasthenic crisis (MC) requiring mechanical ventilation (MV) is a rare and serious complication of myasthenia gravis. Here we analyzed the frequency of performed tracheostomies, risk factors correlating with a tracheostomy, as well as the impact of an early tracheostomy on ventilation time and ICU length of stay (LOS) in MC. Methods: Retrospective chart review on patients treated for MC in 12 German neurological departments between 2006 and 2015 to assess demographic/diagnostic data, rates and timing of tracheostomy and outcome. Results: In 107 out of 215 MC (49.8%), a tracheostomy was performed. Patients without tracheostomy were more likely to have an early-onset myasthenia gravis (27 [25.2%] vs 12 [11.5%], p = 0.01). Patients receiving a tracheostomy, however, were more frequently suffering from multiple comorbidities (20 [18.7%] vs 9 [8.3%], p = 0.03) and also the ventilation time (34.4 days ± 27.7 versus 7.9 ± 7.8, p < 0.0001) and ICU-LOS (34.8 days ± 25.5 versus 12.1 ± 8.0, p < 0.0001) was significantly longer than in non-tracheostomized patients. Demographics and characteristics of the course of the disease up to the crisis were not significantly different between patients with an early (within 10 days) compared to a late tracheostomy. However, an early tracheostomy correlated with a shorter duration of MV at ICU (26.2 days ± 18.1 versus 42.0 ± 33.1, p = 0.006), and ICU-LOS (26.2 days ± 14.6 versus 42.3 ± 33.0, p = 0.003). Conclusion: Half of the ventilated patients with MC required a tracheostomy. Poorer health condition before the crisis and late-onset MG were associated with a tracheostomy. An early tracheostomy (≤ day 10), however, was associated with a shorter duration of MV and ICU-LOS by 2 weeks.